2021
DOI: 10.1001/jamanetworkopen.2021.34330
|View full text |Cite|
|
Sign up to set email alerts
|

Association Between Androgen Deprivation Therapy and Mortality Among Patients With Prostate Cancer and COVID-19

Abstract: IMPORTANCEAndrogen deprivation therapy (ADT) has been theorized to decrease the severity of SARS-CoV-2 infection in patients with prostate cancer owing to a potential decrease in the tissuebased expression of the SARS-CoV-2 coreceptor transmembrane protease, serine 2 (TMPRSS2). OBJECTIVE To examine whether ADT is associated with a decreased rate of 30-day mortality from SARS-CoV-2 infection among patients with prostate cancer. DESIGN, SETTING, AND PARTICIPANTS This cohort study analyzed patient data recorded i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…Patients undergoing ADT have been reported to express lower levels of TMPRSS2, and may be less affected by COVID-19 [103]. Montopoli and colleagues reported an association between ADT and reduced occurrence of SARS-CoV-2 infection, whereas others found no beneficial effect of ADT on SARS-CoV-2 infection or COVID-19 progression [177][178][179][180][181][182]. However, the fact that the study cohorts consisted of men suffering from prostate cancer limits the applicability of the results to non-cancer patients with COVID-19.…”
Section: Clinical Evaluation Of Tmprss2 Inhibitors In Covid-19 Patientsmentioning
confidence: 99%
“…Patients undergoing ADT have been reported to express lower levels of TMPRSS2, and may be less affected by COVID-19 [103]. Montopoli and colleagues reported an association between ADT and reduced occurrence of SARS-CoV-2 infection, whereas others found no beneficial effect of ADT on SARS-CoV-2 infection or COVID-19 progression [177][178][179][180][181][182]. However, the fact that the study cohorts consisted of men suffering from prostate cancer limits the applicability of the results to non-cancer patients with COVID-19.…”
Section: Clinical Evaluation Of Tmprss2 Inhibitors In Covid-19 Patientsmentioning
confidence: 99%
“…Several experiments support the role of co‐receptors and attachment factors such as transmembrane serine protease 2 (TMPRSS2), basigin (BSG) (also known as CD147), GRP78, some toll‐like receptors (TLRs) and c‐type lectin receptors (CLRs), heparan sulfate, and sialic acids, which facilitate and enhance the entry of the virus in the presence of ACE2. 26 , 33 , 36 Nevertheless, these co‐receptors may not be sufficient for virus entry into some specific cells not expressing ACE2 although deletion of co‐receptors may reduce infection. 26 , 33 , 37 , 38 , 39 Furthermore, Neuropilin 1 (NRP1) mainly facilitates the regulation of angiogenesis, gangliogenesis, and vascular permeability, and similarly, enhances viral infectivity and acts as a co‐receptor for cell entry.…”
Section: Mechanism Of Cellular Viral Infectionmentioning
confidence: 99%
“…An early study from Montopoli et al examined 4,532 male patients and found that prostate cancer patients on ADT had lower risk of COVID-19 infection compared to those not on ADT (OR 4.05) [14]. However, newer data from Schmidt et al queried the Cancer Consortium registry and found no difference in 30-day mortality among COVID-19 patients who did and did not receive ADT [12]. Consistent with these data, two recent meta-analysis found no protective effect of ADT against COVID-19 infection or disease severity [33,34].…”
Section: Key Pointsmentioning
confidence: 99%